A new congrid eel, Rhynchoconger randalli sp. nov. (Congridae: Anguilliformes), with a pentagonal pattern of vomer dentition from the Bay of Bengal, Indian waters - Acharya, Smrutirekha; Mohanty, Swarup Ranjan; Ray, Dipanjan; Mishra, Subhrendu Sekhar; Mohapatra, Anil (Zootaxa, 2022)
A new species Rhynchoconger randalli sp. nov. is described herein on the basis of 2 specimens collected from Paradeep fishing harbor, Odisha, India along the Bay of Bengal from a depth of about 36–40 meters. The pentagonal vomerine teeth pattern is unique among all the Rhynchoconger species described to date. The new species is characterized by predorsal vertebrae 7–8 and preanal vertebrae 29–31. The new species closely resembles the recently described Rhynchoconger smithi, but differs in having a larger eye diameter (12.5‒12.9% HL vs. 9.5‒9.7% in R. smithi), smaller interorbital space (13.1‒13.5% HL vs. 15.0‒18.1 in R. smithi), lower dorsal-fin ray count before vent 44‒47 vs. 54‒58 in R. smithi, and unique pentagonal vomerine teeth pattern.